Generation of the Cdk5 activator p25 is a memory mechanism that is affected in early Alzheimer’s disease - Giese, K. Peter (Frontiers in Molecular Neuroscience, 2014)
About 15 years ago it was proposed that generation of the truncated protein p25 contributes to toxicity in Alzheimer's disease (AD). p25 is a calcium-dependent degradation product of p35, the principal activator of cyclin-dependent kinase 5 (Cdk5). The biochemical properties of p25 suggested that its generation would cause Cdk5 overactivation and tau hyperphosphorylation, a prerequisite for neurofibrillary tangle (NFT) formation. Whilst this model was appealing as it explained NFT formation, many laboratories could not confirm the finding of increased p25 generation in brain from AD patients. On the contrary, it emerged that p25 levels are reduced in AD. This reduction occurs primarily in the early stages of the disease. Further, p25 generation in the mouse hippocampus is associated with normal memory formation and p25 overexpression enhances synaptogenesis. Therefore, it transpires that p25 generation is a molecular memory mechanism that is impaired in early AD. I discuss the prospect that investigation of p25-regulated proteins will shed light into mechanisms underlying synaptic degeneration associated with memory decline in AD.